# Chain rule

In calculus, the chain rule is a formula for the derivative of the composition of two functions.

In intuitive terms, if a variable, y, depends on a second variable, u, which in turn depends on a third variable, x; then, the rate of change of y with respect to x can be computed as the product of the rate of change of y with respect to u multiplied by the rate of change of u with respect to x. Suppose, for example, that one is climbing a mountain at a rate of 0.5 kilometre per hour. The temperature is lower at higher elevations; suppose the rate by which it decreases is 6° per kilometre. How fast does the temperature drop? Well, if one multiplies 6° per kilometre by 0.5 kilometre per hour, one obtains 3° per hour. This calculation is a typical chain rule application.

In algebraic terms, the chain rule (of one variable) states that if the function f is differentiable at g(x) and the function g is differentiable at x, and the function F is defined as f composed with g, that is

[itex]
F = f \circ g = f(g(x))


[itex]

then [itex]F'[itex] is given by

[itex]
F' = \frac {dF} {dx} = f'(g(x)) \times g'(x).


[itex]

Alternatively, in Leibniz notation, the chain rule can be expressed as:

[itex]

\frac {dy}{dx} = \frac {dy} {du} \times \frac {du}{dx} [itex] or

[itex]

\frac {d(f \circ g)}{dx} = \frac {d(f \circ g)} {dg} \times \frac {dg}{dx}. [itex]

 Contents

## The general power rule

The general power rule (GPR) is derivable, via the Chain Rule.

### Example I

Consider:

[itex]f\left(x\right) = \left(x^2 + 1\right)^3[itex]

f(x) is comparable to h[g(x)] where g(x) is (x2 + 1) and h(x) is x3; thus,

[itex]f'\left(x\right) = 3\left(x^2 + 1\right)^2\left(2x\right) = 6x\left(x^2 + 1\right)^2.[itex]

### Example II

In order to differentiate the trigonometric function:

f(x) = sin(x2)

one can write f(x) = h(g(x)) with h(x) = sin(x) and g(x) = x2 and the chain rule then yields

f '(x) = cos(x2) 2x

since h '[g(x)] = cos(x2) and g '(x) = 2x.

## Proof of the chain rule

Let f and g be functions and let x be a number such that f is differentiable at g(x) and g is differentiable at x. Then by the definition of differentiability,

[itex] g(x+\delta)-g(x)= \delta g'(x) + \epsilon(\delta)[itex] where [itex] \epsilon(\delta)/\delta\to 0[itex] as [itex]\delta\to 0.[itex]

Similarly,

[itex] f(g(x)+\alpha) - f(g(x)) = \alpha f'(g(x)) + \eta(\alpha)[itex] where [itex]\eta(\alpha)/\alpha \to 0[itex] as [itex]\alpha\to 0.[itex]

Now

[itex] f(g(x+\delta))-f(g(x)) = f(g(x) + \delta g'(x)+\epsilon(\delta)) - f(g(x))[itex]
[itex] = \alpha_\delta f'(g(x)) + \eta(\alpha_\delta)[itex]

where [itex]\alpha_\delta = \delta g'(x) + \epsilon(\delta)[itex]. Observe that as [itex]\delta\to 0,[itex] [itex]\alpha_\delta/\delta\to g'(x)[itex] and [itex]\eta(\alpha_\delta)/\delta\to 0[itex]. Hence

[itex] \frac{f(g(x+\delta))-f(g(x))}{\delta} \to g'(x)f'(g(x))\mbox{ as } \delta \to 0.[itex]

## The fundamental chain rule

The chain rule is a fundamental property of all definitions of derivative and is therefore valid in much more general contexts. For instance, if E, F and G are Banach spaces (which includes Euclidean space) and f : EF and g : FG are functions, and if x is an element of E such that f is differentiable at x and g is differentiable at f(x), then the derivative of the composition g o f at the point x is given by

[itex]\mbox{D}_x\left(g \circ f\right) = \mbox{D}_{f\left(x\right)}\left(g\right) \circ \mbox{D}_x\left(f\right).[itex]

Note that the derivatives here are linear maps and not numbers. If the linear maps are represented as matrices (namely Jacobians), the composition on the right hand side turns into a matrix multiplication.

A particularly nice formulation of the chain rule can be achieved in the most general setting: let M, N and P be Ck manifolds (or even Banach-manifolds) and let f : MN and g : NP be differentiable maps. The derivative of f, denoted by df, is then a map from the tangent bundle of M to the tangent bundle of N, and we may write

[itex]\mbox{d}\left(g \circ f\right) = \mbox{d}g \circ \mbox{d}f.[itex]

In this way, the formation of derivatives and tangent bundles is seen as a functor on the category of C manifolds with C maps as morphisms.

## Tensors and the chain rule

See tensor field for an advanced explanation of the fundamental role the chain rule plays in the geometric nature of tensors.

• Art and Cultures
• Countries of the World (http://www.academickids.com/encyclopedia/index.php/Countries)
• Space and Astronomy